Energy constrained clustering routing method based on particle swarm optimization - Gao, Feng; Luo, Wancheng; Ma, Xinqiang (Cluster computing, 2019)
Wireless sensor networks are made up of a large number of wireless sensor nodes which are exploited to sense parameters in environment such as temperature, moisture level, pressure, light intensity, vibration, and so on. In order to effectively reduce energy consumption of WSN, this paper proposes a novel energy constrained clustering routing method based on particle swarm optimization. The simulation results show that proposed method can achieve better overall performance for both energy consumption and network lifetime.